Patent Strategy in Pharmaceutical Industry: Are additional patents valuable? - Donghi, Monica (Munich Intellectual Property Law Center - MIPLC, 2014)
This book investigates lifecycle management strategies used by pharmaceutical companies attempting to maximize the value of their product portfolio. Such strategies are sometimes referred to by generic drug companies as "evergreening". The analysis focuses on two of these strategies, namely product improvements and product line extensions. In particular, an evaluation of the patents that follow the basic one and that accompany the development of a drug from research to market is attempted. Two "blockbuster" drugs, Taxotere and Xalatan, were randomly chosen to carry out such analysis. The patent portfolio of the originator companies is outlined and some important patents for each area of research (e.g. formulations, combinations, delivery devices) are shortly described. Patent filing trends for the two drugs, both in regards of the originator and in regards of other competing companies (amongst these also the generics) are schematically shown.